1981
DOI: 10.3109/03008208109152372
|View full text |Cite
|
Sign up to set email alerts
|

Immuno Electron Microscopic Studies on Cells Synthesizing Elastin

Abstract: Embryonic chick and hamster aortas were examined in the electron microscope using ferritin-conjugated, elastin-specific antibodies after etching of the plastic, thin sections with a dilute solution of benzene, methanol and ethanol. Specific staining of intracellular vesicles was observed in both smooth muscle and endothelial cells in addition to extracellular elastin fibers. In the chick cells, these ferritin-stained vesicles had a lipid-laden appearance. In both species the vesicles appeared to fuse with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

1982
1982
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…Moreover. Damiano et al [1981] noted intracellular vesicles in the smooth muscle cells which showed a positive reaction to the antielastin antibody. They suggested that elastin is secreted via vesicular structures.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover. Damiano et al [1981] noted intracellular vesicles in the smooth muscle cells which showed a positive reaction to the antielastin antibody. They suggested that elastin is secreted via vesicular structures.…”
Section: Discussionmentioning
confidence: 98%
“…however, is associated with the nonspecific binding of antiserum. The use of a protein such as BSA [Damiano et al, 1981] for pretreatment eliminated nonspecific binding of the primary antiserum to the embedding medium or other tissue components. However, in all cases there were small amounts of nonspecific binding to the embedding medium itself.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors (10) consider that antibodies increase compared to glicated proteins is a marker for speeded age process of vessel wall. It is known that glicated proteins have common epitops (14) and antibodies which react cross-like to different glicated proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Sykes and Chidlow [1974] obtained a good antibody response in sheep to insoluble chicken aorta elastin. Damiano et al [1979Damiano et al [ . 1981 immunized sheep with lung elastin according to the proto col described by Sykes and Chidlow [ 1974] and obtained an antiserum against insoluble elastin.…”
Section: Discussionmentioning
confidence: 99%
“…Sykes and Chidlow [1974] and Damiano et al [1979Damiano et al [ . 1981 used elastin for immunization which was isolated by hot alkaline according to the method of Lansing et al [1952].…”
Section: Discussionmentioning
confidence: 99%